Global Structure and Sodium Ion Dynamics in Mercury's Magnetosphere With the Offset Dipole. Issue 11 (3rd November 2017) - Yagi, M.; Seki, K.; Matsumoto, Y.; Delcourt, D. C.; Leblanc, F.
Abstract: We conducted global magnetohydrodynamics (MHD) simulation of Mercury's magnetosphere with the dipole offset, which was revealed by MESSENGER (Mercury Surface, Space Environment, Geochemistry, and Ranging) observations, in order to investigate its global structure under northward interplanetary magnetic field conditions. Sodium ion dynamics originating from the Mercury's exosphere is also investigated based on statistical trajectory tracing in the electric and magnetic fields obtained from the MHD simulations. The results reveal a north‐south asymmetry characterized by open field lines around the southern polar region and northward deflection of the plasma sheet in the far tail. The asymmetry of magnetic field structure near the planet drastically affects trajectories of sodium ion and thus their pressure distributions and precipitation pattern onto the planet. Weaker magnetic field strength in the southern hemisphere than in the north increases ion loss by precipitation onto the planetary surface in the southern hemisphere. The "sodium ring, " which is formed by high‐energy sodium ions drifting around the planet, is also found in the vicinity of the planet. The sodium ring is almost circular under nominal solar wind conditions. The ring becomes partial under high solar wind density, because dayside magnetosphere is so compressed that there is no space for the sodium ions to drift around. In both cases, the sodium ring is formed by sodium ions that are picked up, accelerated in the magnetosheath just outside the magnetopause, and reentered into the magnetosphere due to combined effects of finite Larmor radius and convection electric field in the dawnside magnetosphere. Key Points: North‐south asymmetry is of paramount importance in the global structure of Mercury's magnetosphere Southward precipitation is dominant for planetary sodium ions High energy "sodium ring" can be formed under nominal solar wind conditions at Mercury's orbit